Management of Skills Programs to Improve the Competencies of Graduates of Learning Citizens - Yanti Nurdiyanti; Neneng Nurmalasari (Universitas Negeri Padang, 2020)
This study aims to determine the pattern of skill management at the Community Learning Activity Center in increasing the competence of graduate learning citizens so that the results of this study are expected to be a reference for the community in an effort to improve the quality of human resources who are competing for people who have not completed formal education up to the school level. Senior High (SMA). This study uses qualitative methods to explore individual behavior in groups and understand the meaning of social problems. The data collection technique was carried out by the method of observation and semistructured interviews on research subjects consisting of PKBM managers, PKBM tutors, and PKBM learning citizens. The data analysis technique used the miles and Huberman model. The results showed: the management of the skills program at PKBM Aykos Nusa Ilmu was carried out by planning, organizing, implementing, and evaluating stages. With the achievement level of competency skills, 80% of graduates meet competency standards, and as many as 20% of graduates show abilities in skills that exceed graduate competency standards.